Pelibatan Masyarakat dalam Persiapan Penetapan Situs Gunung Wingko, Bantul sebagai Cagar Budaya - Anggraeni Anggraeni (Bakti Budaya: Jurnal Pengabdian kepada Masyarakat, 2020)
The use of Gunung Wingko for modern settlements has a significant impact on the preservation of the site. One of the efforts that can be done to prevent the widespread damage to the site is by disseminating important values and determining the site as a cultural heritage. Considering that this stipulation can trigger conflict, it is necessary to carry out careful preparation accompanied by socialization of the values (culture and knowledge) and dialogue with stakeholders through FGD. Sanden Fair, which is an annual event, is one of the means of disseminating research results that have long been carried out at the Mount Wingko Site and the importance of the site. In order to maintain awareness of the importance of the site, an embryo of Gunung Wingko Site Information Center was created. In the future, local communities can be involved in filling out the materials and managing the Information Center that has been initiated. In a FGD involving all stakeholders in Bantul Regency and the DIY Cultural Heritage Conservation Office, it was found that the designation of Gunung Wingko as a cultural heritage was constrained by the absence of site delineation. The Department of Archaeology FIB UGM team proposes gradual protection, starting from the determination of the area of the core zone which refers to the results of previous research. Communities living around the site also need to be involved in the activity of determining Gunung Wingko as a cultural heritage and need to get accurate information about the consequences and impacts of determining the site.====Pemanfatan Situs Gunung Wingko untuk permukiman baru telah membawa dampak yang signifikan terhadap kelestarian situs. Salah satu upaya yang dapat dilakukan untuk mencegah meluasnya kerusakan situs adalah dengan melakukan sosialisasi nilai penting dan penetapan situs sebagai Cagar Budaya. Mengingat penetapan tersebut dapat memicu konflik, maka perlu dilakukan persiapan matang disertai sosialisasi nilai penting (kebudayaan dan pengetahuan) dan dialog dengan para stakeholder melalui FGD. Sanden Fair yang merupakan acara tahunan menjadi salah satu sarana sosialisasi hasil penelitian yang telah lama dilakukan di Situs Gunung Wingko dan nilai penting situs. Guna menjaga kesadaran tentang nilai penting situs tersebut, maka dibuatlah embrio Pusat Informasi Situs Gunung Wingko. Masyarakat setempat ke depan dapat dilibatkan dalam pengisian materi dan pengelolaan Pusat Informasi yang telah dirintis. Dalam FGD yang melibatkan seluruh stakeholder di Kabupaten Bantul dan Balai Pelestarian Cagar Budaya DIY diketahui bahwa penetapan Gunung Wingko sebagai Cagar Budaya terkendala oleh belum adanya delineasi situs. Tim Departemen Arkeologi FIB UGM mengusulkan pelindungan bertahap, dimulai dari penetapan luasan zona inti yang mengacu pada hasil penelitian terdahulu. Masyarakat yang tinggal di sekitar situs juga perlu dilibatkan dalam kegiatan penetapan Gunung Wingko sebagai Cagar Budaya dan perlu mendapat informasi yang tepat mengenai konsekuensi dan dampak penetapan situs.